The new Roget's thesaurus in dictionary form - Lewis, Norman, 1912- (New York, N.Y. : G. P. Putnam's Sons, 1978)
Contains alphabetically arranged entries that provide synonyms of thousands of modern English-language words and terms; and includes cross references.
Adult
Adult
Keywords: English language -- Synonyms and antonyms; English language -- Synonyms and antonyms